Role of small-scale farmers in making agricultural market information systems relevant and sustainable in Bugiri district, Uganda - Kaddu, Sarah; Nanyonga, Doreen; Haumba, Eric Nelson (University of Dar es Salaam Library Journal, 2021)
The study aimed at establishing the role of small-scale farmers in making agricultural market information systems relevant and sustainable in Bugiri district. This study employed a case study research design and adopted a qualitative research approach. Purposive sampling method was used to select respondents with in-depth information and knowledge relating to the topic under study. Data was collected using focus group discussions and unstructured interviews methods. Major findings reveal that market information is still largely focused on prices and does not give details about quality and quantities. Small-scale farmers ' access to and utilization of market information is still limited but gradually improving. There is no systematic infrastructure for timely collection and dissemination of information in an appropriate medium to all stakeholders. The study concludes that value chain development is crucial for the success of market information systems and it is therefore imperative that information be provided on different areas along the chain. The study recommends establishment of village/parish information centres and display boards to inform small-scale farmers about up-to-date market information.